2015
DOI: 10.12710/cardiometry.2015.7.2229
|View full text |Cite
|
Sign up to set email alerts
|

Activation therapy: theoretical and applied aspects

Abstract: The paper presents a brief review on how some concepts on the organism general adaptational reactions developed, including their role in increasing the unspecific resistance in the organism. Demonstrated is periodicity of the patterns of anti-stressor type reactions (training, calm and elevated activation) and stress in a wide range of stimulation values. The concepts on the organism adaptational reactions and reactivity levels have created the theoretical basis for practical applications of the activation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
1
6
0
4
Order By: Relevance
“…The results, obtained during studying micro pictures of thymus and spleen under the RR ef fective influence, corresponded to the information in literature concerning changes in the immune system organs in case of tumor regressions under the effect of activation therapy with ultralow frequency EMRs [3,4,12]. As opposed to hypoplasia and degenerative disorders, typical for thymus and spleen under tumor stress ( Fig.1А and 2А), in the cases of effective influ ence of resonance EMR in these organs high lymph oproliferative activity (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The results, obtained during studying micro pictures of thymus and spleen under the RR ef fective influence, corresponded to the information in literature concerning changes in the immune system organs in case of tumor regressions under the effect of activation therapy with ultralow frequency EMRs [3,4,12]. As opposed to hypoplasia and degenerative disorders, typical for thymus and spleen under tumor stress ( Fig.1А and 2А), in the cases of effective influ ence of resonance EMR in these organs high lymph oproliferative activity (Fig.…”
Section: Resultssupporting
confidence: 76%
“…The electromagnetotherapy course duration is 3.5-4 weeks. The actions have been carried out in accor dance with the activation therapy principles [3][4][5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Этот факт способствовал тому, что прокальцитонин стали использовать в качестве маркера бактериальных инфекций. В отличие от всех известных маркеров воспаления, метод определения прокальцитонина более чувствителен и высокоспецифичен для тяжелой бактериальной инфекции [9][10][11][12][13][14]. Дрожжевые грибы рода Candida spp -одни из самых распространенных возбудителей инвазивных микозов.…”
Section: Introductionunclassified
“…They were independent, separate symptom complexes and other discrete states. It has been found that in response to a relatively weak influence, an adaptive symptom complex is formed, which is called "the reaction of training"; "the reaction of activation" is a response to a medium, intermediate between strong and weak, stimulus [9,10].…”
Section: Introductionmentioning
confidence: 99%